2015
DOI: 10.1104/pp.15.00899
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Rice MicroRNA528 Alters Plant Development and Enhances Tolerance to Salinity Stress and Nitrogen Starvation in Creeping Bentgrass

Abstract: MicroRNA528 (miR528) is a conserved monocot-specific small RNA that has the potential of mediating multiple stress responses. So far, however, experimental functional studies of miR528 are lacking. Here, we report that overexpression of a rice (Oryza sativa) miR528 (Osa-miR528) in transgenic creeping bentgrass (Agrostis stolonifera) alters plant development and improves plant salt stress and nitrogen (N) deficiency tolerance. Morphologically, miR528-overexpressing transgenic plants display shortened internodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 92 publications
6
105
0
1
Order By: Relevance
“…With the growth of rice, the expression of miR528 increased in the leaves. It has been reported that overexpression of osa-miR528 in transgenic creeping bentgrass ( Agrostis stolonifera ) changed the plant development and improved the plant tolerance to salt stress and nitrogen (N) deficiency [55]. Morphologically, miR528-overexpressing transgenic plants display shortened internodes, increased tiller numbers, and upright growth [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growth of rice, the expression of miR528 increased in the leaves. It has been reported that overexpression of osa-miR528 in transgenic creeping bentgrass ( Agrostis stolonifera ) changed the plant development and improved the plant tolerance to salt stress and nitrogen (N) deficiency [55]. Morphologically, miR528-overexpressing transgenic plants display shortened internodes, increased tiller numbers, and upright growth [55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of osa-miR528 in transgenic creeping bentgrass ( Agrostis stolonifera ) changed the plant development and improved the plant tolerance to salt stress and nitrogen (N) deficiency [55]. Morphologically, miR528-overexpressing transgenic plants display shortened internodes, increased tiller numbers, and upright growth [55]. Furthermore, overexpression of osa-miR528 in transgenic rice reduced the rice tolerance to Arsenic (As) stress, and the amino acid contents changed and the oxides increased both in the shoots and roots [56].…”
Section: Discussionmentioning
confidence: 99%
“…The plants and the sand were flushed using sufficient water to remove residual nutrients and then natured using modified 19 Murashige and Skoog (MS) solution supplemented with N at different concentrations (0, 0.4, 2, 10 or 40 mM). The preparation of MS solution and N addition was as previously described (Yuan et al, 2015). Three and five weeks after N starvation treatment, the shoots were harvested for further analysis to examine expression of the genes of interest and measure various physiological parameters.…”
Section: Plant Transformation Propagation Maintenance and Stress Trmentioning
confidence: 99%
“…The nitrite content was calculated from a KNO 2 standard curve. NiR activity was determined following Yuan et al (2015).…”
Section: Measurement Of Reduced Trx Content and Nir Activitiesmentioning
confidence: 99%
“…All these indicate that miRNAs are master regulators in plant response to various environmental cues and may have great potential in crop genetic engineering for enhanced plant performance under adverse environmental conditions. Indeed, this has been demonstrated for an increasing number of miRNAs, such as miR319, miR528, miR396 and miR408 (Chen et al ., ; Ma et al ., ; Yuan et al ., ; Zhou et al ., ). Recently, a conserved miRNA, miR393 has been identified with the potential of mediating plant response to a variety of biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%